2022
DOI: 10.1002/jcph.2170
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors and Tuberculosis Infection in Lung Cancer: A Case Series and Systematic Review With Pooled Analysis

Abstract: The association between immune checkpoint inhibitors (ICIs) and tuberculosis (TB) infection in patients with lung cancer remains largely elusive. We performed a systematic review and conducted a retrospective analysis of TB infection in patients with lung cancer and ICI exposure to assess the clinical characteristics and outcomes using PubMed, EMBASE, and the Cochrane Library. The time interval from ICI administration to diagnosis of TB between patients with and without a history of TB was compared using Kapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…However, when treating cancer patients who also suffer from infections, the use of immunotherapy should be approached with caution. Recently, several cases of TB infection activation in cancer patients receiving ICIs treatment have been reported, [19][20][21][22][23] According to a meta-analysis, the incidence of TB was 35 times higher in PD-1/PD-L1 blockade-treated patients than in the general population. [24] Meanwhile, another observational study revealed that among patients with cancer, the incidence of TB in the group exposed to ICIs was 675.8 per 100,000 person-years (95% confidence interval: 412.8-1043.8), while in the non-exposure group, it was 599.1 per 100,000 person-years (95% confidence interval: 560.5-639.6).…”
Section: Discussionmentioning
confidence: 99%
“…However, when treating cancer patients who also suffer from infections, the use of immunotherapy should be approached with caution. Recently, several cases of TB infection activation in cancer patients receiving ICIs treatment have been reported, [19][20][21][22][23] According to a meta-analysis, the incidence of TB was 35 times higher in PD-1/PD-L1 blockade-treated patients than in the general population. [24] Meanwhile, another observational study revealed that among patients with cancer, the incidence of TB in the group exposed to ICIs was 675.8 per 100,000 person-years (95% confidence interval: 412.8-1043.8), while in the non-exposure group, it was 599.1 per 100,000 person-years (95% confidence interval: 560.5-639.6).…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing ICIs administration are eight times more likely to contract TB than the general population, according to an observational study ( 49 ). A Meta-analysis revealed that patients receiving PD-1/PD-L1 in developed Asian countries were 35 times more likely to develop TB than general population ( 50 ).…”
Section: Etiology Of Fever Of Unknown Origin Induced By Icismentioning
confidence: 99%
“…TB infection following ICIs therapy lacks specificity, and is usually characterized by cough, expectoration, breathlessness, fever and weight loss ( 49 , 53 ). Imaging manifestations, from chest X-ray and contrast CT, support the diagnosis with features like new consolidation, patchy opacity/nodules, or the tree-in-bud sign, especially in the upper lobes ( 49 ). However, confirmation is achieved by culture of MTB or DNA detection by polymerase chain reaction (PCR) ( 52 , 55 ).…”
Section: Etiology Of Fever Of Unknown Origin Induced By Icismentioning
confidence: 99%
See 1 more Smart Citation